Using XhLEA, a group 1 vegetative Late Embryogenesis Abundant protein to aid water deficit tolerance in plants and microbes - Denkhaus, Erik (Stellenbosch : Stellenbosch University, 2015)
Thesis (MSc)--Stellenbosch University, 2015.